Patchwork Capitalism (Remarks on the Sidelines of the Concept put forward by Juliusz Gardawski and Ryszard Rapacki) - Gumuła, Wiesław (Warsaw Forum of Economic Sociology, 2022)
This article presents a critical analysis of the concept of patchwork capitalism and the resulting methodological perspective created by Juliusz Gardawski and Ryszard Rapacki. The authors conducted extensive research, resulting in new theoretical and methodological tools that they used to study capitalism in Central and Eastern Europe. An important research result is the development of the ideal type of capitalism in the Weberian sense of the term. I think that at this stage of research, the authors have provided insufficient arguments to verify the hypothesis of the patchwork nature of Central European capitalism. However, there are also no grounds for rejecting it. This is a matter for further research. The concept of patchwork capitalism inspires academic debate. It is a very promising theoretical proposal that can be used both to verify and falsify hypotheses about the patchwork nature of institutional economic arrangements in various national economies.